Pengaruh Islamic Corporate Philantropy terhadap Kinerja Bank Umum Syariah di Indonesia Serta Analisis Kepatuhan pada Undang-undang Zakat dan Tanggung Jawab Sosial - Ely Masykur; Niswatul Hidayati (ACTIVA: Jurnal Ekonomi Syariah, 2019)
This research is motivated by the gap between the potential of zakat and realization in the community. So this study aims to provide empirical evidence of the influence of Islamic corporate philanthropy on the performance of Islamic public banks in Indonesia. Furthermore, this study tries to analyze the compliance with the implementation of Law Number 23 of 2011 concerning the Management of Zakat, the Act Article 74 number 40 of 2007 and about social responsibility as an obligation that must be budgeted and calculated as the company's operational costs. The sample of this study were 12 Islamic banks registered in OJK. Secondary data used in this study was taken from the annual report of the 2011-2017 period that was audited and published. Data analysis techniques using regression and analysis of legal interpretation. The results of the research show that there is a significant influence between ICP and the performance of Islamic banks and there is a sample banking compliance in the applicable legislati